From Niche To Mainstream: A Strategic Analysis Of Halal-Centric Muslim-Friendly Element Development In International Tourism - Hisham Sabri; Nur Ainna Ramli; Sharifudin Md Shaarani; Muhammad Nizam Awang; Nurul Asyiqin Akmarulazham (Universal Publishers - Boca Raton, Florida, USA, 2026)
Indexed by ERA